Traces of Orientalism in the Construction of Modern Islamic Science - Ahmad Hidir Amin; Hamdanah Hamdanah; Mazrur Mazrur (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study examines traces of Orientalism in the construction of modern Islamic scholarship as an epistemological issue in contemporary Islamic studies. The main focus of the study is to identify how categories of knowledge, standards of truth, and scholarly authority regarding Islam are formed, institutionalised, and reproduced in modern academic traditions. The research uses a qualitative method based on a literature study with a historical-critical approach to academic texts from three traditions: classical Orientalists, post-Orientalist thinkers, and Muslim scholars. The data are analysed comparatively to trace patterns of continuity and transformation of epistemic categories used in Islamic studies. The results show that modern Islamic studies operate within the framework of epistemic categories such as objectivity, historicism, textual criticism, and scientific methodology rooted in Western scientific traditions. Islamic scientific traditions tend to gain academic legitimacy to the extent that they can be translated or harmonised with these categories. The dominance of Orientalism is therefore not only a historical legacy but also works structurally through the university system, curriculum, and mechanisms of publication and global scientific legitimacy. This study contributes by systematically mapping these epistemic mechanisms, thereby expanding the analysis of Orientalism from the level of discourse representation to the level of operational structures in contemporary academic practice